Modeling the Broad-Band Emission from the Gamma-Ray Emitting Narrow-Line Seyfert-1 Galaxies 1H 0323+342 and B2 0954+25A - Arrieta-Lobo, Maialen; Boisson, Catherine; Zech, Andreas (Frontiers in Astronomy and Space Sciences, 2017)
Prior to the Fermi-LAT era, only two classes of Active Galactic Nuclei (AGN) were thought to harbor relativistic jets that radiate up to gamma-ray energies: blazars and radio galaxies. The detection of variable gamma-ray emission from Narrow Line Seyfert 1 (NLSy1) galaxies has put them on the spotlight as a new class of gamma-ray emitting AGN. \textbf{In this respect, gamma-ray emitting NLSy1s seem to be situated between blazars (dominated by non-thermal emission) and Seyferts (accretion disc dominated). In this work, we model the Spectral Energy Distribution (SED) of two gamma-loud NLSy1s, 1H 0323+ 342 and B2 0954+25A, during quiescent and flaring episodes via a multi-component radiative model that features a relativistic jet and external photon fields from the torus, disk, corona and Broad Line Region (BLR). We find that the interpretation of the high-energy emission of jetted NLSy1s requires taking into account Inverse Compton emission from particles in the relativistic jet that interact with external photon fields. Minimal changes are applied to the model parameters to transition from average to flaring states. In this scenario, the observed variability is explained mainly by means of changes in the jet density and Doppler factor.